An ethics of responsibility reading of Eduard Tödt’s theory of the formation of moral judgement - De Villiers, Etienne (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
In the article the interpretation of Eduard Tödt’s theory of the formation of moral judgements as descriptive of the six steps that are logically presupposed in the formation of all moral judgements is critically discussed. On the basis of an analysis of the four publications in which Tödt developed his theory it is demonstrated in the first part of the article that such an interpretation is incorrect. The normative nature of his theory is acknowledged. In the second part of the article a case is made for an ethics of responsibility reading of his theory. Each of the six steps in the process of the formation of moral judgements that Tödt distinguishes, is analysed. It is demonstrated that each of these steps entails a distinctive normative ethical approach that can be depicted as ethics of responsibility.